Cultural awareness and the global hospitality business - Mkono, Muchazondida (Cognizant Communication Corporation, 2021)
In the contemporary hospitality business, cultural awareness has become an important source of competitive advantage. With the proliferation of multinational hospitality firms, there is cutthroat competition: it is a "survival of the fittest" game. Hospitality firms can outsmart and outperform each other based on how well they know the cultures of their present and potential markets, as well as the cultural backgrounds of their staff members. A "one size fits all" approach has proved redundant in contemporary international business. This article discusses the role of cultural awareness in business success and sustainability of the hospitality business. A case study on Hilton's "Wa No Kutsurogi" brand is presented to enable the author to comment on, and draw parallels between, theory and practice from an empirical standpoint. It is argued that consumption of hospitality products (food and accommodation) is a culture-driven activity, and only those products that interact with customers' "cultures" at an emotional level will appeal to them. The article suggests that culture should be understood in a broad sense: there are several levels and dimensions to culture. The discussion emphasizes the need to customize hospitality products in accordance with the cultural dynamics of niche markets.